The effect of legal representation on clinical measures in involuntarily admitted psychiatric patients: a retrospective study - Yaacov Cohen; Ariel L. Bendor; Roy Gilbar; Orly Cohen; Razek Khawaled; Arieh Dienstag; Amit Lotan; Omer Bonne (BMC, 2024)
Abstract Background Most western countries provide funded legal representation (LR) for involuntarily admitted psychiatric patients appearing before judicial committees. In 2004, an amendment to the Israeli Mental Health Act granted this right to involuntarily committed psychiatric patients. Psychiatrists then voiced concerns that LR may increase rates of premature discharge and compromise patients' safety and well-being. These worries have not been sufficiently addressed to date. This study aimed to provide answers to their concerns. Methods This study included 3124 and 3434 inpatients involuntarily admitted to psychiatric facilities in 2000 and in 2010 (respectively), prior to and after the introduction of LR in Israel. Data were acquired from the Israeli National Psychiatric Hospitalization Registry. Clinical measures included percentage of discharges by the District Psychiatric Board (DPB), duration of involuntary hospitalization and rates of readmissions within thirty days and six months of discharge by treating psychiatrists (TP) or DPB. Results The odds ratio (OR) of discharge by a DPB in 2010 (n = 221) compared to 2000 (n = 93) was 2.2 [95%CI 1.72-2.82]. The OR was similar for readmissions within thirty days or six months among patients discharged by TP and a DPB (OR = 1.08, p = 0.697 and OR = 0.92, p = 0.603, respectively) as well as between the two time points (p = 0.486 and p = 0.618). The duration of hospitalizations terminated by a DPB was significantly shorter than those terminated by TP, with no difference between the study time points. The mean hospitalization duration in 2010 was 21% shorter compared to 2000 among patients discharged by TP. Conclusions The number of DPB proceedings and the number of involuntarily hospitalized psychiatric patients discharged by DPBs increased considerably after the advent of state-funded legal representation in 2004. We found that this did not compromise beneficence and non-malfeasance of patient care. Our results emphasize the feasibility of affording even the most severely mentally ill patients the rights to due process. These findings may relieve concerns about state-funded LR procedures in involuntary psychiatric hospitalizations.